Educational Institutions of Islamabad during COVID-19 Pandemics: A Reflective Study - Malik, Parveen Akhter; Dilshad, Saadia (American Journal of Education and Practice, 2022)
Purpose: The spread of Novel Corona virus (COVID-19) affected all fields of life along with education across the globe. After increase in positive cases of COVID-19, Federal Government of Pakistan announced the closure of educational institutions all over the country in the mid of March, 2020, as a protective measure for students and staff members. Due to complete lockdown in the country, internal and board exams of secondary school certificate (SSC) and higher secondary school certificate (HSSC) cancelled. Students got promotion without annual examination into next classes based on previous performance. This study investigated the blow of COVID- 19 on the students of government educational institutions of Islamabad along with the response of Government on the issue. Methodology: This was a qualitative study with case study approach. Target population was all the students and teachers/head teachers from public High and Higher secondary schools in Islamabad Pakistan. Random convenient sampling technique used for collection of data. Semi structured interviews were conducted telephonically for data. After completion, interviews/ responses transcribed and analyzed. Findings: Results of this research have revealed that this pandemic has badly affected the Federal educational institutions of Islamabad because of confinement of students in homes. Generally, students in government schools are from middle and lower middle class. They have no/limited access to internet and technology at home. It has widened the gap between privileged and none privileged/less privileged students due to inequality in access to internet and unavailability of gadgets in unbiased access to quality education. These factors compelled the Government to launch Tele-School on PTV (Pakistan Television) channel that started its regular transmission on 14 April 2020. Basic aim was to give assistance to all students confined at home. Schools opened after expected peak time I.e. 15 September. Students were allowed to join the regular school in small groups on alternate day. Strict precautionary measures, like social distancing, use of disinfectants in and around the premises/humans and provision of regular medical assistance carried out. Data revealed that the whole system was overburdened but the steps taken caused the far less damage than expected to the students. Recommendation: The study recommend that Tele-school channel should continue even after pandemic. It is beneficial for students to learn during closure of schools. It is also helpful to the students of remote areas, with no or least of internet facilities. Time has proven that the low-income government institutions have tackled the situation very well under the visionary umbrella of Federal Directorate of Education Islamabad Pakistan.